2019
DOI: 10.1007/s11127-019-00741-0
|View full text |Cite
|
Sign up to set email alerts
|

Partisan bias in inflation expectations

Abstract: We examine partisan bias in inflation expectations. Our dataset includes inflation expectations of the New York Fed's Survey of Consumer Expectations over the period June 2013 to June 2018. The results show that inflation expectations were 0.46 percentage points higher in Republican-dominated than in Democratic-dominated US states when Barack Obama was US president. Compared to inflation expectations in Democratic-dominated states, inflation expectations in Republican-dominated states declined by 0.73 percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…We also contribute to studies that investigate how government ideology influences macroeconomic outcomes and expectations (e.g. Santa-Clara and Volkanov, 2003;Gerber and Huber, 2010;Blinder and Watson, 2016;Cahan and Potrafke, 2017;Potrafke, 2017Potrafke, , 2018Bachmann et al, 2020;Pastor and Veronesi, 2020). Examining how government ideology in the United States influences expectations about economic outcomes in other countries is new.…”
Section: Introductionmentioning
confidence: 99%
“…We also contribute to studies that investigate how government ideology influences macroeconomic outcomes and expectations (e.g. Santa-Clara and Volkanov, 2003;Gerber and Huber, 2010;Blinder and Watson, 2016;Cahan and Potrafke, 2017;Potrafke, 2017Potrafke, , 2018Bachmann et al, 2020;Pastor and Veronesi, 2020). Examining how government ideology in the United States influences expectations about economic outcomes in other countries is new.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the severity and timing of the imposition of the containment measures themselves could depend on the political leaning of the state governments. At the same time, these political leanings could have affected inflation beliefs independently of the containment measures (Bachmann et al 2021 ). As a robustness check, we omitted individuals that reside in the five states 10 that flipped from Republican to Democrat at the 2020 US Presidential Election and re‐estimated our regressions.…”
Section: Estimation and Resultsmentioning
confidence: 99%
“…Inflation expectations may also depend on political attitudes, see, for example, Bachmann et al. (2021) and the literature cited therein. Recently, Gillitzer, Prasad, and Robinson (2021) showed that U.S. and Australian consumers expect significantly lower inflation when the political party they support holds executive office.…”
Section: Inflation Expectations and The Pandemic: The Role Of Persona...mentioning
confidence: 99%